Effects of Transformational and Transactional Leadership on Employee’s Innovative Behavior: Mediating Effect of Employee’s Goal Orientations - Wong, Boon Yew (American Scientific Publishers, 2017)
Employee’s innovative behavior is increasingly recognized as an important driver for organization’s competitiveness and survival. Transformational and transactional leadership have been argued to be positively and negatively related to employee’s innovative behavior respectively. However, the empirical evidences for the arguments appear to be inconsistent, with some finding positive, negative, and even no effect. These findings suggest that the understanding of the relationship between transformational and transactional leadership and innovative behavior may benefit from the identification of mediating and moderating variables that can provide a better understanding of “how” and “when” transformational and transactional leadership are effective or ineffective in influencing employee’s innovative behavior. Addressing this issue, based on the review of existing literatures, this study proposes a conceptual model underpinned by social cognitive theory to explore the direct effect of transformational and transactional leadership and the indirect effect through employee’s goal orientations on employee’s innovative behavior.